Optimal management of postoperative parenchymal air leaks - French, Daniel G.; Plourde, Madelaine; Henteleff, Harry; Mujoomdar, Aneil; Bethune, Drew (Journal of Thoracic Disease; Vol 10, Supplement 32 (November 20, 2018): Journal of Thoracic Disease (Enhanced Recovery: The Evidence Supporting Best Perioperative Care in Thoracic Surgery), 2018)
Air leaks are the most common complication after pulmonary resection. Enhanced recovery after surgery (ERAS) programs must be designed to manage parenchymal air leaks. ERAS programs should consider two components when creating protocols for air leaks: assessment and management. Accurate assessment of air leaks using traditional analogues devices, newer digital drainage systems, portable devices and chest X-rays (CXR) are reviewed. Published data suggests that digital drainage systems result in a more confident assessment of air leaks. The literature regarding the management of postoperative air leaks, including the number of chest tubes, the role of applied external suction, invasive maneuvers and discharge with a portable device is reviewed. The key findings are that a single chest drain is adequate in the majority of cases to manage an air leak, the use of applied external suction is unlikely to prevent or prolong an air leak, autologous blood patch pleurodesis may potentially shorten postoperative air leaks and there is sufficient data to support that patients can safely be discharged with a portable drainage system. There is also literature to support the design of protocols for management of postoperative air leaks. Standardization of postoperative care through ERAS programs will allow for the design of larger RCTs to better understand some of the controversies around the management of postoperative air leaks.